2021
DOI: 10.1007/s13205-020-02615-5
|View full text |Cite
|
Sign up to set email alerts
|

Advances in biotechnology of Emblica officinalis Gaertn. syn. Phyllanthus emblica L.: a nutraceuticals-rich fruit tree with multifaceted ethnomedicinal uses

Abstract: Emblica officinalis Gaertn. syn. Phyllanthus emblica L., universally known as ‘Amla’ or ‘Aonla’ or ‘Indian gooseberry’, is a popular fruit tree belonging to the family Euphorbiaceae and order Geraniales. It is said to be the very first tree that originated on earth, as claimed by age-old Indian mythology. Almost all parts of the tree i.e., root, bark, leaf, flower, fruit and seed are utilized in Ayurvedic and Unani medicinal formulations to improve the overall digestive process, decrease fever, act as a blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 99 publications
0
24
0
Order By: Relevance
“…Polyphenols, tannins, flavonoids, and ascorbic acid are the primary antioxidants and bioactive components found in amla fruit [19,21,22]. Serum albumin is a multi-functional protein that can bind and transport numerous endogenous and exogenous compounds [64], and is also believed to act as an antioxidant because of free radical scavenging to protect bound substances from peroxidative damage, such as FA and lipoproteins [65].…”
Section: Blood Biochemical Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyphenols, tannins, flavonoids, and ascorbic acid are the primary antioxidants and bioactive components found in amla fruit [19,21,22]. Serum albumin is a multi-functional protein that can bind and transport numerous endogenous and exogenous compounds [64], and is also believed to act as an antioxidant because of free radical scavenging to protect bound substances from peroxidative damage, such as FA and lipoproteins [65].…”
Section: Blood Biochemical Parametersmentioning
confidence: 99%
“…syn. Phyllanthus emblica L., universally known as 'Amla' or 'Aonla' or 'Indian gooseberry', is a popular fruit tree belonging to the family Euphorbiaceae and order Geraniales [19]. Amla originates from India but is also cultivated in several other tropical and sub-tropical countries such as Bangladesh, China (southern part), Malaysia, Mascarene Islands, Myanmar, Pakistan, Sri Lanka, and Uzbekistan [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emblica officinalis Gaertn. ; Family Phyllanthaceae) because of its ethnopharmacological uses for more than 5000 years in Ayurvedic medicine originated in India [13]. The plant is cultivated and distributed to nearby countries such as Bangladesh, China, Thailand and other Southeast Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…Several articles have reported that YGZ and its extracts could protect RAW264.7 cells from H 2 O 2 -induced toxicity, reduce the size of atherosclerotic plaques, and inhibit endothelin-1 (ET-1) expression. [33][34][35] Moreover, it could exert antiinflammatory effects by reducing the expression of nitric oxide (NO) and proinflammatory cytokines. 36 In addition, it could protect β-cells, scavenge-free radicals, alleviate inflammation, and reduce advanced glycation end products.…”
Section: Discussionmentioning
confidence: 99%